ANALISIS SUBSTITUSI AGGREGAT KASAR MENGGUNAKAN LIMBAH BAN PADA CAMPURAN BETON TERHADAP KUAT TEKAN BETON - Yodi Gusti Fernandes; Ishak Ishak; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2022)
problems, one of which is the problem of environmental impacts resulting from the use of aggregates or materials from nature that cannot be renewed by utilizing waste rubber tires as a concrete mixture. This is because considering that there is a lot of waste rubber tires in Indonesia, with this waste treatment it will certainly reduce the waste generated from waste rubber tires. type and compressive strength, the percentage of waste rubber tires used is 5%, 10%, and 15% of the volume of coarse aggregate, making samples using cubes of 15cm x 15cm x 15cm as many as 9 samples with a concrete age of 7 days, 14 days, and 28 day. The method used in this study is a qualitative method (research at the laboratory of the Muhammadiyah University of West Sumatra). By replacing some of the coarse aggregate using waste tires as much as 5% produces a compressive strength of 141.01 kg/cm², 10% produces a compressive strength of 137.44 kg/cm², and 15% produces a compressive strength of 110.66 kg/cm² at the age of 28 days. .Which with a mixture of waste tires makes the compressive strength decrease from normal concrete which has a compressive strength of 251.67 kg/cm² at the age of 28 days. But the compressive strength of normal concrete increases from the planned concrete quality, namely K-250 to 251.67 kg/cm². Keywords : compressive strength, coarse aggregate, interlocking, waste rubber tires.